To Buy or Not to Buy? A Research on the Relationship Between Traceable Food Extrinsic Cues and Consumers’ Purchase Intention - Li Ge (Frontiers in Psychology, 2022)
With the prevalence of traceability technology in the turbulent Internet age, traceable food has become an important tool in addressing food safety issues. Under the combined effect of frequent food safety problems and sustainable development of traceability industry, the research on traceable food consumer behavior has become more extensive. However, it is still not fully understood how the multiple information brought by traceability affects consumers’ purchase decision. This study proposes the effects of traceability knowledge, traceable information quality and traceable certification credibility on traceable food purchase intention via the mediation of perceived risk and perceived value, and integrates the moderating effect of peer influence in the context of Internet age into a research framework. The analytical results indicate that traceability knowledge, traceable information quality, and traceability certification credibility indirectly affect consumers’ traceable food purchase intention through perceived risk and perceived value, while traceability knowledge, perceived risk, and perceived value directly affect “traceable food purchase intention.” Furthermore, peer influence was found to be a significant moderator in the relationship between perceived risk (perceived value) and “traceable food purchase intention.” Finally, based on the research results, traceability companies are suggested to focus on cultivating the traceable consumption habits. Meanwhile, although traceable food quality is the top priority, companies should also attach importance to the communication and interaction with consumer.